Multi-flex neo-hybrid identities : liberatory postmodern and (post) colonial narratives of South African women's hair and the media construction of identity - Le Roux, Janell Marion (My University, 2020)
Hair has been a marker of identity that communicates issues of race, acceptability, class and beauty. Evidence of this was during colonialism and apartheid where South African identities were defined by physical characteristics such as the texture of one’s hair, and the colour of one’s skin. Whiteness was the epitome of beauty which came with certain privileges. Non-White bodies were defined as part of a particular narrative that saw them as well as their hair as inferior to that of White bodies. Academic literature continues to engage African hair from the perspective of a colonial legacy through a postcolonial lens. This study, however, asserts a shift in engaging African hair and introduces an African identity which is re-empowered and liberated through agency and choice, and active participation in the construction of its own identity. This shift in engagement also relinquishes the African identity’s association with the dominant narrative of its conformity to a single European ideology of beauty and identity by introducing a (post)colonial, postmodern theory of a Multi-flex, Neo-hybrid identity which forms part of the theoretical framework of this study. This study draws on the theoretical positions of postmodern theory about the concepts of ‘self’ and identity. It engages interpretations of postmodernism and ‘self’ through the works of Kenneth Gergen and Robert Lifton who provide critical theoretical insight into postmodernism and identity. It also engages critical scholars such as Homi Bhabha, Franz Fanon, Kwame Appiah, Charles Ngwenya and Achille Mbembe, amongst others. Through this theoretical lens, I examine the role of the media in the presentation of the panoply of hair (styles) to South African women in the process of constructing a fluid, flexible and hybrid identity that decentres the ideology of rigid racial identity. I also critically investigate whether non-White women who lived during the colonial-apartheid era and those born in a free democratic era share this multi-flex, neo-hybrid identity of the postmodern woman. Thus this study aims to critically explore social narratives of South African women’s hair and how the media perpetuate the construction of a new postmodern African female identity within the backdrop of the commodification of hair and identity in a globalised market and media environment. Coupled with an interpretivist paradigm, a phenomenological v approach was adopted for this study. Data was collected from print media content material namely, DRUM Hair magazine (editions 2014-2019) due to the assortment of hairstyles and identities it provides for African women. Data was also collected in the form of semi-structured interviews/personal accounts/stories presented as phenomenological narratives from colonial-born Coloured and colonial-born Black female participants. Focus group interviews were conducted on post-apartheid/born-free Coloured and Black female South African participants to understand how these women construct their identities through hairstyle choices and the impact this has on the (re)presentation of their identities within the global beauty market environment. These diverse participants aged from 18 to 104 allow me to trace, if any, the changes in perception of hair and hairstyles from colonial-apartheid South Africa to the new and free post-apartheid South Africa. The results of the study show that media enable the African woman to construct a postmodern identity through the multiplicity of hairstyles/identities available to her. It also provides the African woman with the tools to create various identities for herself through the diversity of hairstyles available to her. The African woman who is exposed to an assortment of hairstyles can navigate from one identity to the next without being loyal to one identity which is typical of the postmodern self. Another finding is that coloniality seems to continue to shape the identities of women born during the colonial apartheid era. But for those born during the (post)colonial and post-apartheid era, they embrace a navigatory form of hybridity that is not loyal to one identity but explores various forms of identity, which the market place affords them and the media perpetuate in the construction of multi-flex, neo-hybrid and postmodern identities. The implication of this study is that it is liberating since it allows us to critically review our identity and what we deem as beautiful and to question the daily choices we make not only with our hairstyles but with fashion, food and other cultural elements that shape our performance of identities.
Thesis (Ph.D. Communication Studies)) -- University of Limpopo, 2020
Keywords: Hair as identity; Racial imbalances; Colour segregation; Black women's beauty; Hair; Black people -- Race identity; Apartheid -- South Africa -- History; Hair -- Analysis